Impact of E-Learning Orientation, Moodle Usage, and Learning Planning on Learning Outcomes in On-Demand Lectures - Saori Aida (MDPI AG, 2023)
The growing prominence of e-learning in education has led to the need for a comprehensive understanding of the factors influencing learning outcomes. This study aims to investigate the combined effects of e-learning orientation, Moodle usage, and learning planning on learning outcomes in the context of on-demand lectures. A sample of participants from the Department of Information Science and Engineering in the Faculty of Engineering completed questionnaires related to e-learning orientation, while Moodle usage data and learning planning information were collected. Correlation, principal component, cluster, and multiple regression analysis were conducted to examine the relationships between variables and their impact on learning outcomes. The results suggest that e-learning orientation did not exert a significant influence on learning outcomes. However, Moodle usage and learning planning emerged as crucial factors. Increased engagement with Moodle, as indicated by higher clicks and utilization of its learning functionalities, was associated with improved learning outcomes. Additionally, effective learning planning, characterized by adherence to schedules and timely submissions, positively influenced learning outcomes. The results emphasize the importance of considering multiple factors, not just a single factor, for successful online learning. These findings provide valuable insights for optimizing learning outcomes in on-demand lectures.